Регіональні тематичні словники етнокультури українців: методи та принципи створення, результати - Пономар, Л. (Матеріали до української етнології, 2015)
У статті акцентується увага на необхідності створення словників в етнології для відображення результатів сучасних наукових досліджень. Зразком такого нового підходу є регіональні тематичні словники в доробку українських діалектологів кінця ХХ ст. На особливу увагу заслуговують ті, що базуються на атласних матеріалах. На прикладі словника народного одягу Правобережного Полісся показано значення форми розгорнутого атласу для створення етнографічних словників з метою комплексного подання термінів і реалій. В статье акцентируется внимание на необходмости создания словарей в этнологии для представления результатов современных научных исследований. Примером такого нового подхода являются региональные тематические словари украинских диалектологов конца ХХ ст. Особое внимание заслуживают словари, которые отражают материалы региональных атласов. На примере словаря одежды Правобережного Полесья показано значение формы развёрнутого атласа для создания этнографических словарей с целью комплексной подачи терминов и реалий. The article deals with the requirement to create new lexicons in ethno logy with the view of reflecting the results of modern scientific studies. The example of a new approach to material representation is the thesauri of creation of the late 20th-century Ukrainian dialectologists. Among them, worthy of particular attention are those that were based on atlas materials. The example of the dictionary of folk clothing of Right-Bank Polissya shows the importance of the form of an expanded atlas for creating ethnographic dictionaries with the aim of a comprehensive presentation of terms and realities. Of informative value are the correlations of names with separate types of clothes and the ascertainment of regional and local features of realia and their names. The lexicon has a description of attire from Western and Central Polissia and its names, along with reference to maps, as well as its semantics, etymology, and designation against the All-Ukrainian background, together with its connections with other Slavic languages.